Hypnobirthing Relaxation and Prenatal Yoga in Reducing Anxiety Levels Among Pregnant Women in Third Trimester - Puspitasari, Lutfiana; Rosalina, Rosalina (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2023)
Empowering pregnant women through education on pregnancy and delivery, including interventions such as Hypnobirthing and prenatal yoga, is essential to alleviate anxiety and promote a healthy pregnancy. This study aims to assess the impact of hypnobirthing and prenatal yoga on anxiety levels in pregnant women during their third trimester. The research employed an observational analytical experimental approach, utilizing a randomized control trial design. It was conducted in the independent practice of midwives in the Klaten regency from March to June 2020. The population in this study was all pregnant women who were in the working area of the Kebondalem Lor health centre, whose gestational age was above 28 weeks, a total of 120 respondents. The study employed simple random sampling for participant selection and univariate analysis. Statistical bivariate tests using the paired and independent sample test were also conducted. There was a significant difference in decreasing anxiety after pregnant women in the third trimester did Hypnobirthing and Prenatal Yoga, with a p-value of 0.001. There was a significant difference between Hypnobirthing and Prenatal Yoga in decreasing anxiety, with a p-value of 0.01. Additionally, prenatal yoga was found to be more effective in reducing anxiety than hypnobirthing.